2022
DOI: 10.1001/jamanetworkopen.2022.20689
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Timing of Noncardiac Surgery After Transcatheter Aortic Valve Implantation

Abstract: This cohort study investigates the association of surgery and valve factors with adverse outcomes of noncardiac surgery following transcatheter aortic valve implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…While there are not any agreed on guidelines regarding the timing of non-cardiac surgeries status post-TAVR, a recent cohort study suggested that the timing of non-cardiac surgery after TAVR was not associated with increased risk of adverse events, except in instances of prosthesis-patient mismatch and paravalvular regurgitation 19. Therefore, the decision to perform the tumour resection 6 weeks after the TAVR was based on patient choice.…”
Section: Discussionmentioning
confidence: 99%
“…While there are not any agreed on guidelines regarding the timing of non-cardiac surgeries status post-TAVR, a recent cohort study suggested that the timing of non-cardiac surgery after TAVR was not associated with increased risk of adverse events, except in instances of prosthesis-patient mismatch and paravalvular regurgitation 19. Therefore, the decision to perform the tumour resection 6 weeks after the TAVR was based on patient choice.…”
Section: Discussionmentioning
confidence: 99%
“…They found that patients without prior AVR had significantly higher rates of red blood cell transfusions (26.4% vs. 15.8%), a higher use of Swan-Ganz monitoring (16.7% vs. 5.5%), and higher catecholamine utilization (16.7% vs. 1.5%) ( 16 ). Although urgent non-cardiac surgery is typically associated with unfavorable hemodynamics, Okuno et al demonstrated a borderline significant association between the risk of the 30-day composite outcome associated with urgent non-cardiac surgery after TAVR (58.6% vs. 43.8%, p = 0.05), but this association was not significant on multivariable analysis [adjusted hazard ratio (aHR): 1.60 (95% CI: 0.94–2.73), p = 0.08] ( 17 ). Given the borderline p -values, this may reflect a lack of statistical power for the identification of increased risk among patients undergoing urgent surgery, and larger studies are required to explore this further.…”
Section: Risks Involved With Asymptomatic and Symptomatic Patients Wi...mentioning
confidence: 99%
“…The timing of non-cardiac surgery after AVR is another important aspect to be considered. A prospective single-center cohort study looked at the timing and risks of non-cardiac surgery after TAVR, with most of the patients undergoing intermediate-risk non-cardiac surgery ( 17 ). The study included 21.0% who underwent non-cardiac surgery within 30 days of TAVR, 25.0% between 31 days and 180 days, 23.0% between 181 days and 365 days, and 31.0% more than 1 year after TAVR ( 17 ).…”
Section: Selection Of Valve Intervention Strategymentioning
confidence: 99%
See 2 more Smart Citations